On Neuropsychiatric Manifestations of Basal Ganglia Injury: A Report of Three Cases and Literature Review - Heela Azizi; Alexander Kilpatrick; Olaniyi Olayinka; Olusegun Poopola; Maleeha Ahmad; Alexa Kahn; Tasmia Khan; Dina Rimawi; Shantale Williams; Sinthuja Jayaraj; Ivan Leung; Sherina Langdon; et al. (Case Reports in Neurological Medicine)
The basal ganglia have been considered to primarily play a role in motor processing. A growing body of theoretical and clinical evidence shows that in addition to the motor functions the basal ganglia play a key role in perceptual and visual disturbances. This role may be evident in patients with basal ganglia pathology and subsequent manifestation of symptoms that include cognitive, perceptual, and affective disturbances. We present three cases with basal ganglia pathology that demonstrate affective and psychotic symptoms. Two of the cases presented with late onset psychotic disturbances suggesting likely neurological etiologies. The third case presented with treatment refractory psychosis and symptoms that are rare for a diagnosis of schizophrenia. The role of incidental bilateral basal ganglia calcifications in all the cases is discussed. A review of current literature highlighting various neuropsychiatric manifestations of basal ganglia pathologies in various patients with psychiatric symptoms is presented.